Epsilon aminocaproic acid (EACA) myopathy. Issue 642 (April 1979) - Lane, R. J.; McLelland, N. J.; Martin, A. M.; Mastaglia, F. L.
Abstract : Two female patients developed a severe, painful proximal myopathy after taking 18–30 g of epsilon-aminocaproic acid daily for 5 weeks. Marked elevations of serum aminotransferases, creatine kinase and aldolase levels were found and the first patient had electromyographic and muscle biopsy changes of an acute monophasic, necrotising myopathy at the height of the illness. Resolution occurred in both cases on stopping the drug and the second patient had no electromyographic or muscle biopsy abnormalities 3 weeks later. Only 2 recognized cases of the condition have been reported previously but a review of the literature revealed several other possible examples.